Gastritis staging in the endoscopic follow-up for the secondary prevention of gastric cancer: a 5-year prospective study of 1755 patients. Issue 1 (6th January 2018) - Rugge, Massimo; Meggio, Alberto; Pravadelli, Cecilia; Barbareschi, Mattia; Fassan, Matteo; Gentilini, Maria; Zorzi, Manuel; Pretis, Giovanni De; Graham, David Y; Genta, Robert M
Abstract : Objective: Operative link on gastritis assessment (OLGA) staging for gastritis ranks the risk for gastric cancer (GC) in progressive stages (0–IV). This prospective study aimed at quantifying the cancer risk associated with each gastritis stage. Design: A cohort of 1755 consecutive patients with dyspepsia underwent initial (T-0) oesophagogastroduodenoscopy with mapped gastric biopsies, OLGA staging and assessment of Helicobacter pylori infection. Patients were followed for 55 months (median); patients with stages II III and IV underwent a second endoscopy/restaging (T-1), and those with stages 0 and I were followed clinically and through in-depth clinical and record checking. Endpoints were OLGA stage at T-1 and development of gastric epithelial neoplasia. Results: At T-0, 77.6% of patients had stage 0, 14.4% stage I, 5.1% stage II, 2.1% stage III and 0.85% stage IV. H. pylori infection was detected in 603 patients at T-0 and successfully eradicated in 602 of them; 220 had a documented history of H. pylori eradication; and 932 were H. pylori naïve-negative. Incident neoplastic lesions (prevalence=0.4%; low-grade intraepithelial neoplasia (IEN)=4; high-grade IEN=1; GC=2) developed exclusively in patients with stages III–IV. The risk for epithelial neoplasia was null in patients at stages 0, I and II (95% CI 0 to 0.4), 36.5 per 1000 person-years in patients at stage III (95% CI 13.7 to 97.4) and 63.1 per 1000 person-years in patients at stage IV (95% CI 20.3 to 195.6). Conclusions: This prospective study confirms that OLGA staging reliably predicts the risk for development of gastric epithelial neoplasia. Although no neoplastic lesions arose in H. pylori- naïve patients, the H. pylori eradication in subjects with advanced stages (III–IV) did not abolish the risk for neoplastic progression.